MENCETAK MUZAKKI BARU MELALUIOPTIMALISASI PROGRAM KOMUNITAS USAHA MIKRO MUAMALAT BERBASIS MASJID - Syarifudin, Moh (IAIN Ambon, 2019)
Paper aims to determine KUM3 program in Jayapura and how the pattern of this program to realize the Mustahik Zakat becomes Muzakki. Powerlessness is something that is fought by Islam with the potential of charity and charity. The right formulation is needed so that the effort to empower the economy of the people effectively, efficiently and certainly optimal in order to provide benefits that are right on target and effective rather than the opposite which makes recipients lazy and unproductive. Mosque-Based Muamalat Micro Business Community (KUM3) in Jayapura City is one of the programs of the BMM in collaboration with the Muamalat Bank of Jayapura City Branch. in the city of Jayapura and how the pattern of the program is to turn the Mustahik Zakat into Muzakki. This research by the author uses a qualitative approach, the emphasis is not on testing hypotheses but on efforts to answer research questions through formal and argumentative thinking. This study has natural characteristics and is field work and is descriptive in nature. The findings in this study are that the Jayapura City KUM3 is the application of the financing of Qordhul Hasan which is managed directly by BMM with Bank Muamalat as a companion and supervisor. From the data of 75 Mustahik, about 95% of them have completed their loans and 75% of them are ready to become Muzakki. In the long run Muzakki will be directed to form the Syari'ah Financial Services Cooperative (KJKS) in Jayapura. Market eviction, stalls eviction, lack of mobility must be prepared and mental preparedness, skills and motivation are obstacles to the optimal program. Although not yet 100%, but this is one of the project is a model for print Mustahik be Muzaki Keywords: economic empowerment, KUM3, mustahik, muzakki